2014
DOI: 10.1007/s10745-014-9655-7
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Over Space and Time: Fishing Effort Allocation and the Development of Customary Norms in an Open-Access Mangrove Estuary in Ecuador

Abstract: Fisheries are increasingly understood as complex adaptive systems; but the cultural, behavioral, and cognitive factors that explain spatial and temporal dynamics of fishing effort allocation remain poorly understood. Using Geographic Information Systems (GIS) as a visualization tool, this paper combines catch-per-unit-effort (CPUE) and ethnographic data about the Ecuadorian mangrove cockle fishery to explore patterns in fishing effort and the social production of fishing space. I argue that individual decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 65 publications
0
21
0
4
Order By: Relevance
“…Locals refer to the fishing grounds managed as common property as "las areas," which lie somewhere between the boundaries of Zones 1 and 2. The cultural features of these zones were further elaborated in a previous study of the fishing effort in Isla Costa Rica, which revealed an informal division of fishing space based on personal preferences, habitual use, and mutual respect among individual cockle collectors from the community and beyond (see Beitl, 2014, for a more in-depth ethnographic description of the fishery). Grouping fishing grounds into these four zones was necessary in this study to further discern patterns of mobility and explore how fishers navigate over fishing space under formal and informal governance systems in Isla Costa Rica.…”
Section: Description Of Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Locals refer to the fishing grounds managed as common property as "las areas," which lie somewhere between the boundaries of Zones 1 and 2. The cultural features of these zones were further elaborated in a previous study of the fishing effort in Isla Costa Rica, which revealed an informal division of fishing space based on personal preferences, habitual use, and mutual respect among individual cockle collectors from the community and beyond (see Beitl, 2014, for a more in-depth ethnographic description of the fishery). Grouping fishing grounds into these four zones was necessary in this study to further discern patterns of mobility and explore how fishers navigate over fishing space under formal and informal governance systems in Isla Costa Rica.…”
Section: Description Of Study Areamentioning
confidence: 99%
“…Optimal foraging models contain several assumptions, but the two assumptions most relevant to this research are: 1) that fishers have perfect information about the "quality" of fishing grounds and 2) the availability of resources within those fishing grounds will decline with accelerating gains, similar to the subtractability problem in the commons literature. While fishers do not have perfect information about the environment, it is relatively safe to assume that fishers in Isla Costa Rica have a specialized understanding about their preferred fishing grounds, which developed out of habitual use (Beitl, 2014). Based on these two assumptions, this study tests the following hypotheses: H1: Cockle collectors switch fishing grounds when their catch rate drops below the average gross return rate for all the fishing grounds in the environment.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoy hay numerosos trabajos socioambientales que se desenvuelven en el medio costero y marino. Los más numerosos analizan la pesca desde puntos de vista espaciales (Beitl, 2014), arqueológicos (Prieto, 2017), históricos (Cariño y Monteforte, 2005), administrativos (Dunn et al, 2016), etnográficos (Early Capistrán, 2010), políticos (Beitl, 2012) y sociológicos (Hannigan, 2017).…”
Section: Las Oceanografías Sociales: Evolución De Un Campo De Estudiounclassified
“…However, I would argue that other production systems with similar characteristics also have open property regimes, for example, foragers (Myers 1982;Bliege Bird et al 2016) and fishers (St. Martin 2001;Beitl 2014). Of course, I am referring here to production systems that are primarily aimed at subsistence and which have low capital inputs, and not, for example, to industrial cod fisheries.…”
Section: Key Characteristics Of Open Property Regimesmentioning
confidence: 99%